Evidentiary Strength of Electronic Evidence in Civil Disputes within the Framework of Bayyinah: A Case Study of Decision No. 22/PDT.G/2021/PN DGL - Valentdava Wahyudi, Aurell; Winanti, Atik (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2026)
Background: The advancement of information technology in the digital era has introduced new dimensions to legal proceedings, particularly through the emergence of electronic evidence. This includes screenshots of digital conversations, electronically produced documents, and other forms of digital records. These new evidentiary types have begun to play a significant role in civil litigation, including inheritance disputes. In the Indonesian legal system, the increasing reliance on electronic documents presents both opportunities and challenges. Questions arise concerning the admissibility, authenticity, and legal force of such evidence, especially in sensitive cases like inheritance, where traditional documentation is often favored. This paper specifically addresses the complexity surrounding the evaluation and use of electronic evidence in Indonesian civil courts, emphasizing its growing importance in delivering justice in the modern legal landscape. Purpose: This study examines the judicial assessment of electronic evidence in inheritance disputes through a case study of Decision No. 22/PDT.G/2021/PN DGL at the Donggala District Court. The research aims to analyze how electronic communications, particularly WhatsApp chats, are evaluated as valid proof under Indonesian civil procedural law and their relevance to the Islamic legal concept of bayyinah. Methods: Using a normative juridical approach with statute and case analysis, the study reviews primary legal sources, including the Civil Code, the Herziene Indonesisch Reglement (HIR), and the Electronic Information and Transactions (EIT) Law, complemented by secondary literature Results: The findings reveal that the court recognized electronic evidence as valid proof when it met formal requirements (printing, stamping, and verification) and material requirements (relevance and uncontested authenticity). The Defendants’ electronic submissions were deemed legally sufficient to prove the transfer of property during the decedent’s lifetime, whereas the Plaintiff’s evidence was rejected for lack of probative value. Implication: The study highlights the need for clearer judicial guidelines, enhanced digital forensic literacy among judges, and legal reforms such as digital notarization and certified e-filing systems to strengthen evidentiary reliability in line with Sharia principles. Originality: The novelty of this research lies in its integration of electronic evidence within the framework of Islamic procedural law, interpreting digital communications as a modern manifestation of bayyinah.